Chaperone Hsp70 helps Salmonella survive infection-relevant stress by reducing protein synthesis. - Carissa Chan; Eduardo A Groisman (PLoS Biology)
In all domains of life, Hsp70 chaperones preserve protein homeostasis by promoting protein folding and degradation and preventing protein aggregation. We now report that the Hsp70 from the bacterial pathogen Salmonella enterica serovar Typhimurium-termed DnaK-independently reduces protein synthesis in vitro and in S. Typhimurium facing cytoplasmic Mg2+ starvation, a condition encountered during infection. This reduction reflects a 3-fold increase in ribosome association with DnaK and a 30-fold decrease in ribosome association with trigger factor, the chaperone normally associated with translating ribosomes. Surprisingly, this reduction does not involve J-domain cochaperones, unlike previously known functions of DnaK. Removing the 74 C-terminal amino acids of the 638-residue long DnaK impeded DnaK association with ribosomes and reduction of protein synthesis, rendering S. Typhimurium defective in protein homeostasis during cytoplasmic Mg2+ starvation. DnaK-dependent reduction in protein synthesis is critical for survival against Mg2+ starvation because inhibiting protein synthesis in a dnaK-independent manner overcame the 10,000-fold loss in viability resulting from DnaK truncation. Our results indicate that DnaK protects bacteria from infection-relevant stresses by coordinating protein synthesis with protein folding capacity.